Analysis of Factors Affecting Poverty in the North Sumatra Province - Arif Rahman; M Syafii; Sukma Hayati Hakim (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
North Sumatra is the province with the largest number of poor people in 2019 with the fifth highest poverty percentage on the island of Sumatra. This province has a good potential for accelerating economic growth and improving the quality of life if all levels of society are empowered with all their capabilities in carrying out productive business activities, and can access to socio-economic resources. This study aimed to determine and analyze the effect of the real GDP per capita variable, the open unemployment rate, and the average length of schooling simultaneously and partially on the poverty rate in 33 cities and regencies of North Sumatra Province in 2017-2019. It used secondary data using the Eviews program, while analysis technique used was panel data regression. Based on the research results, it was found that the real GDP per capita, the open unemployment rate, and the average length of schooling simultaneously had a significant effect on the poverty level. Per capita real GRDP and average length of schooling partially had a negative and significant effect on poverty rate. Meanwhile, the open unemployment rate had no significant effect on poverty. The variable that has the most dominant influence on the level of poverty was real GDP per capita.